The Influence of SME Tuing-Tuing Fish Culinary Tourism on the Level of Community Welfare: Case Study from Sendana Sub-District, Majene Regency, Indonesia - Rahayu Umar, Sri; Heryati, Yati; Ridwan Hayadin, Muh. (Golden Ratio of Social Science and Education, 2024)
The objectives of this study are to examine the partial effect of Tuing-Tuing Fish Culinary Tourism SME on the level of community welfare in Parabaya Hamlet, Onang Village, Sendana District, Majene Regency, and to analyze the correlation between Tuing-Tuing Fish Culinary Tourism SME and community welfare in the same area. This research adopts a quantitative approach with one independent variable and one dependent variable. The test tools used in this study include validity tests, reliability tests, multiple linear regression tests, t-tests (partial tests), and R² tests.The sample for this study consisted of 30 respondents. Research data was processed using simple linear regression analysis with SPSS version 24.0 software to determine the direction and strength of the independent variable’s influence on the dependent variable, as well as to conduct the t-test (partial test) and R² test. The results indicate that Tuing-Tuing Fish Culinary Tourism SME have a partial effect on the level of community welfare in Parabaya Hamlet, Onang Village, Sendana District, Majene Regency. Furthermore, the findings show a strong correlation between Tuing-Tuing Fish Culinary Tourism SME and the level of community welfare in the studied area.